Effect of entomopathogenic fungus Beauveria bassiana (balsamo) Vuillemin on the control of sheep ked (Melophagus ovinus) - Valbuena Puentes, Adrián Hernando (2021)
Melophagus ovinus (sheep ked) is a common parasite of sheep, its control is based on chemical treatments; however, the environmental and public health consequences require the application of alternative treatments such as entomopathogenic fungi. The study aimed to determine the effect of the fungus Beuveria bassiana on the parasite in naturally infested sheep. Fifteen adult Hampshire crossbred sheep were used, randomly distributed in three spray treatments with dilutions: T1: 3.2 x108 conidia/ml, T2: 3.2x108 conidia/ml + 5% sugar and control T: distilled water. The daily parasites were counted on the animal to determine the population density and the efficacy of the treatments. The population density was controlled from day 14 with B. bassiana, reducing the presence of ked by 90% (T1 and T2), compared to 5.9% in the T Control (p<0.05). The study suggests that B. bassiana works with an efficacy of 89.3% for the control of M. ovinus. Key words: biological control, false tick, sheep, efficacy, in vivo